2021
DOI: 10.1038/s41467-021-22291-0
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical reduction of acetonitrile to ethylamine

Abstract: Electrifying chemical manufacturing using renewable energy is an attractive approach to reduce the dependence on fossil energy sources in chemical industries. Primary amines are important organic building blocks; however, the synthesis is often hindered by the poor selectivity because of the formation of secondary and tertiary amine byproducts. Herein, we report an electrocatalytic route to produce ethylamine selectively through an electroreduction of acetonitrile at ambient temperature and pressure. Among all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
80
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 46 publications
(44 reference statements)
1
80
0
Order By: Relevance
“…Further, as the reaction onset is limited by the Pd hydrogenation potential, it is possible to carry out the reaction before the thermodynamic potential for the hydrogen evolution reaction is reached. This offers a substantial advantage over a conventional electrosynthetic scheme where, for example, onset potentials for a variety of metallic catalysts were on the order of -0.3VRHE 17,18 , with our work offering an improvement of 0.7V over this value.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…Further, as the reaction onset is limited by the Pd hydrogenation potential, it is possible to carry out the reaction before the thermodynamic potential for the hydrogen evolution reaction is reached. This offers a substantial advantage over a conventional electrosynthetic scheme where, for example, onset potentials for a variety of metallic catalysts were on the order of -0.3VRHE 17,18 , with our work offering an improvement of 0.7V over this value.…”
Section: Resultsmentioning
confidence: 84%
“…S3). This is a remarkable improvement as recent screening of various metallic catalysts indicated that their onset of catalytic activity for acetonitrile hydrogenation is ~0.7V more negative than this 17,18 . We noted that if instead of using 'wet' acetonitrile with 60mM H2O present we added in 0.2% (V:V) 0.5M H2SO4, our partial current density more than doubled.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…1 H NMR spectrum of the reaction product showed CH3CH2NH2 as a major product and minor fractions of (CH3CH2)2NH and (CH3CH2)3N side products (Fig. 1e) (18,19). This confirmed CH3CN can be effectively converted to CH3CH2NH2 via electrochemical hydrogenation.…”
Section: Resultsmentioning
confidence: 96%